Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Berpikir Kritis Peserta Didik pada Mata Pelajaran Biologi - Damayanti, Mesra; Fauzan, Muhammad Miftah; Jirana, Jirana; Sidira, Sidira (Journal of Health, Education, Economics, Science, and Technology, 2025)
The Guided Inquiry Learning Model is an approach that emphasizes the process of discovering concepts and the relationships between them in a systematic manner. This study aims to examine the impact of the guided inquiry learning model on the critical thinking skills of students in class XII MIPA at SMAN 1 Campalagian. This research uses a quantitative method with a quasi-experimental design. The sample consists of 69 students selected through cluster random sampling. The data collection instrument was an essay-type test designed to measure critical thinking skills. Data analysis was performed using the Independent Sample T-Test in SPSS version 23. The results show that there is a significant influence of the guided inquiry learning model on students' critical thinking skills, as evidenced by a significance value of 0.04 < 0.05. Therefore, H₀ is rejected and H₁ is accepted, indicating that the guided inquiry learning model significantly improves students' critical thinking skills.